PENGARUH PEMBERIAN BIOKOMPOS (BAHAN AKTIF Trichoderma sp., FORMULA SEDIAAN TABLET) TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Umrah Umrah; Firji Della Sugeha; Miswan Miswan (Biocelebes, 2015)
This research were performed to find out the effect of bio-compost treatment (Trichoderma sp. active material, formula of tablet-form) towards the cacao seedling’s growth.This research has been conducted between June-August 2014, at Langaleso Village, Kecamatan Dolo, districtof Sigi, Provinsi of Central Sulawesi. This research was designed in form of six treatments and threereplication according to Completely Randomized Design.The design of treatments is mixture of soil and bio-compost Trichoderma sp. active material formula of tablet-form, which P0 (soil without bio-compost as control), P1 (mixture of soil and bio-compost with 5 tablets per kg substrate Trichoderma sp. active material), P2 (10 tablets per kg substrate), P3 (15 tablets per kg substrate), P4 (20 tablets per kg substrate), and P5 (25 tabletsper kg substrate). The Parameter observed includes plant hight (cm) and number leafs (sheet) that observed in each week during six weeks, biomass plant dryweight (g) that observed in sixth week. The result of reseach showed that bio-compost treatment (Trichoderma sp. Active material formula tablet-form) indicate significant effect to cacao seedling. The conclusion is P5 treatment are the best among the other treatments including control, according to the growth rate wereon plant height (22,40 cm), number of leafs (9,67) and biomass plant dryweight (2,12 g).Keywords : cacao seedling, bio-compost, Trichoderma sp.